2015
DOI: 10.5194/nhess-15-1381-2015
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the link between drought indicators and impacts

Abstract: Abstract. Current drought monitoring and early warning systems use different indicators for monitoring drought conditions and apply different indicator thresholds and rules for assigning drought intensity classes or issue warnings or alerts. Nevertheless, there is little knowledge on the meaning of different hydro-meteorologic indicators for impact occurrence on the ground. To date, there have been very few attempts to systematically characterize the indicator-impact relationship owing to sparse and patchy dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 46 publications
4
109
0
1
Order By: Relevance
“…It is however noted that such analysis would require a good quality of impact variable data sets and, for many regions for which we need reliable and accurate data sets (e.g., on groundwater drought information), these observations are often not readily available. Nevertheless, the issue of analyzing an appropriate drought timescale is not only specific for the groundwater system, but is also relevant for several other hydrological and ecological systems (e.g., Pasho et al, 2010;Vicente-Serrano et al, 2011López-Moreno et al, 2013;VicenteSerrano et al, 2013;Haslinger et al, 2014;Bachmair et al, 2015;Van Loon, 2015). Figure 5 shows the exemplary time series of the SGI and SPI at 6 and 12 months of the accumulation periods for all wells and grid cells and their respective spatial averages for an overlapping period of 1995-2006.…”
Section: Spi With Spatially Uniform Accumulation Periodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is however noted that such analysis would require a good quality of impact variable data sets and, for many regions for which we need reliable and accurate data sets (e.g., on groundwater drought information), these observations are often not readily available. Nevertheless, the issue of analyzing an appropriate drought timescale is not only specific for the groundwater system, but is also relevant for several other hydrological and ecological systems (e.g., Pasho et al, 2010;Vicente-Serrano et al, 2011López-Moreno et al, 2013;VicenteSerrano et al, 2013;Haslinger et al, 2014;Bachmair et al, 2015;Van Loon, 2015). Figure 5 shows the exemplary time series of the SGI and SPI at 6 and 12 months of the accumulation periods for all wells and grid cells and their respective spatial averages for an overlapping period of 1995-2006.…”
Section: Spi With Spatially Uniform Accumulation Periodsmentioning
confidence: 99%
“…In recent years there have been some efforts to analyze the relationship between meteorological and groundwater-based drought indices (Bloomfield and Marchant, 2013;Folland et al, 2015;Bachmair et al, 2015). Bloomfield and Marchant (2013), for example, introduced the Standardized Groundwater level Index (SGI), similar to the SPI, and found a site-specific relationship between the two indices.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Kingston et al (2015) found that a higher number of European droughts was identified by the SPEI than by the SPI. Likewise, Bachmair et al (2015) found higher correlations for SPEI than for SPI. The findings by Bachmair et al (2015), Stagge et al (2015a) and Blauhut et al (2016) similarly suggest that SPEI tends to be a better predictor of drought impacts than SPI, but a combination of different aggregation periods and indices generally is considered most favorable.…”
Section: Comparison Of Different Types Of Datamentioning
confidence: 87%
“…Likewise, Bachmair et al (2015) found higher correlations for SPEI than for SPI. The findings by Bachmair et al (2015), Stagge et al (2015a) and Blauhut et al (2016) similarly suggest that SPEI tends to be a better predictor of drought impacts than SPI, but a combination of different aggregation periods and indices generally is considered most favorable. In the given case, however, the behavior of the SPEI only minimally deviates from the SPI, as can be seen from the high correlation between the two indices (see Fig.…”
Section: Comparison Of Different Types Of Datamentioning
confidence: 87%
“…as a result of infrastructure failures, health and psychological impacts) can also be difficult to assess. More geographically explicit damage relationships are needed for hazards such as droughts (Bachmair et al, 2015;Blauhut et al, 2015) or tsunamis (Goda and Song, 2016), which 20 cover potentially large and heterogeneous areas. Potential sources of damage are even more difficult to estimate for future events, as a result of epistemic uncertainties (e.g.…”
Section: Uncertainty Quantification Related To the Consequences Of Namentioning
confidence: 99%